Altered Brain Functional Network Topology in Lung Cancer Patients After Chemotherapy - You, Jia; Zhang, Juan; Shang, Song'an; Gu, Wei; Hu, Lanyue; Zhang, Yujie; Xiong, Zhenyu; Chen, Yu-Chen; Yin, Xindao (Frontiers in Neurology, 2021)
Purpose: This study aimed to explore the topological features of brain functional network in lung cancer patients before and after chemotherapy using graph theory. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) scans were obtained from 44 post-chemotherapy and 46 non-chemotherapy patients as well as 49 healthy controls (HCs). All groups were age and gender-matched. Then topological features of brain functional network were assessed using graph theory analysis. Results: At the global level, compared with the HCs, both non-chemotherapy group and post-chemotherapy group showed significantly increased values in sigma (p<0.05), gamma (p<0.05) and local efficiency Eloc (p<0.05). The post-chemotherapy group and the non-chemotherapy group did not differ significantly in above parameters. At the nodal level, when non-chemotherapy or post-chemotherapy patients compared with the HCs, abnormal nodal centralities were mainly observed in widespread brain regions. However, when the post-chemotherapy group compared with non-chemotherapy group, significantly decreased nodal centralities were observed primarily in the prefrontal-subcortical regions. Conclusions: These results indicate that lung cancer and chemotherapy can disrupt topological features of functional networks, and chemotherapy may cause a pattern of prefrontal-subcortical brain network abnormality. As far as we know, it is the first report that altered functional brain networks are related to lung cancer and chemotherapy.